PHONOLOGICAL SYSTEM OF BALINESE LANGUAGE USED IN PEDAWA VILLAGE, BULELENG REGENCY, BALI - ., Iga Putu Ardaba Kory; ., Dr. I Gede Budasi, M.Ed.; ., Nyoman Karina Wedhanti, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This qualitative research describes Phonological system of Balinese language. The aim of this study was 1) To find out the vowel phonemes of Balinese language in Pedawa Dialect and their distribution, 2) To find out the diphthong Balinese language used in Pedawa dialect, 3) To find out the consonant phonemes of Balinese language in Pedawa dialect and their distribution, 4) To find out the consonant clusters that are used in Pedawa dialect. The main instrument was the researcher, and the researcher also used the other instruments namely, recorder and a word list. The data were gathered by conducting observation, recording and interview techniques. The result of this research can be describe that (1) there were 28 phonemes of Balinese language in Pedawa dialect. Those phoneme were /ʌ/, /i/, /u/, /e/, /o/, /ǝ//p/, /b/, /t/, /d/, /k/, /g/, /ʔ/, /s/, /c/, /j/, /l/, /h/, /m/, /n/, /ñ/, /ŋ/, /r/, /w/, /y/ /ʌi/, /ʌe/, /ʌɛ/ that consist of 6 vowels, 3 diphthongs and 19 consonants. (2) The researcher also found 2 consonant clusters in of Balinese language in Pedawa dialect which were they are /r/ and /kl/keyword : Dialect, Pedawa, Phonological System